Challenging the aid paradigm Western currents and Asian alternatives - SoÌ?rensen, Jens Stilhoff (Houndsmills, Basingstoke, Hampshire New York Palgrave Macmillan, 2010)
"Challenging the Emerging Aid Paradigm critically examines central aspects of Western international aid policy, while at the same time exploring non-western especially Chinese aid and assesses to what extent these may be competitive or complementary"-- Provided by publisher.
Machine generated contents note: Introduction: Challenges to an Emerging Aid Paradigm--J.S.Sörensen * The Development-Security Nexus: Mapping the Landscape--M.Stern * Fragile States: Aid in a Post-Interventionary Age--M.Duffield * A Critical Review of the NGO Sustainable Development Philosophy--V.Pupavac * Aid Policy, Civil Society and Ethnic Polarization--J.S.Sörensen * Local Perceptions of External Peace-Building in Bosnia-Herzegovina--R.Kostic * Is There an Alternative Asian model of Aid?--M.Söderberg * Chinas Aid to Africa: Policy Evaluation, Characteristics and its Role--H.Wenping * -- Chinese Eyes on Africa: Good Governance versus Effective Governance--J.Lagerkvist * Chinese Development Assistance in West Africa: The Cases of Mali and Mauritania--Y.Mohamed-Mahmood * Chinese Africa Policy: Any Impact on the Aid Paradigm?--H.Melber.
Includes bibliographical references and index.
Tac-1708g donated by Prof. Pauline Eadie on 10 September 2015.
Keywords: Economic assistance, European -- Developing countries; Economic assistance, Chinese -- Developing countries